Integrity and Transparency: Public Perceptions of Religious Values Education in a Plural Society - Yusuf Siswantara; Ace Suryadi; Mupid Hidayat; Ganjar Muhammad Ganeswara (Jurnal Theologia, 2022)
In various countries, diversity impacts social conflicts in various forms, not ethnicity, ideology, but also religion. Although many conflicts are based on diversity in Indonesia, religion is the most accessible and most conflict-prone social identity. To address the issue, tolerance or moderation education has widely campaigned. However, the rise of intolerance indicates an unformed factor, namely the perception or attitude toward religious life. Therefore, it is essential to research religious life attitudes. This study aims to analyze the perception of religious life on claims of truth, uniqueness, relations of other religions, and global ethics. For this reason, the combined method with embedded design is a choice of approach from this study. Data collection is carried out simultaneously, both qualitatively and quantitatively. The analyses of the two were combined to get a complete picture of the respondents' religious perceptions or attitudes. The renewal of this study, in addition to empirical studies on the religious attitudes of millennials, is the relationship between perceptions/attitudes of religious life to the relationship between religions through global ethical issues as a common problem. The conclusions of this study are, (1) respondents see a global problem, but at the same time, there is a universal value in religion, (2) With this universal value belief, respondents tend to be open to dialogue because they believe there is goodness in religions, (3) For the problem of dogma teachings, respondents tend to be exclusive without closing the truth of other religions. The suggestions given, among others, are (1) religious education raises the dimension of global ethics, both humanitarian and ecological; (2) religious education builds a dialogical religious attitude with three conditions: understanding one's religion (the uniqueness and peculiarities of faith), being open to other religions, and offering the value of faith to overcome the global problem